Environmental impact assessment of power production with the EcoSense model - Molnár, Sándor; Sleiszné Csábrági, Anita (Acta Agraria Kaposváriensis, 2010)
In the paper an overview is presented of external costs of power production and the respective methodological tools applied to assess such costs, together with air quality models. An overview is then given of the external costs of nuclear energy utilisation, and focusing on power production environmental impacts of alternative capacity extension scenarios are assessed utilising results from EcoSense based on the long term expansion plans of the Hungarian Transmission System Operator (MAVIR).
Keywords: impact assessment; external costs; power production